Lavoura arcaica: interdito, transgressão e erotismo no corpo da linguagem - Santos, Ana Beatriz Germano (2014)
The main focus of this study is the two parts of the novel Lavoura arcaica, emphasizing the conflictive relation between André and his father, Iohána. Characterized by anger and rebellion in his discourse against his father s principles, André returns to family environment, but actually questions it. He resents himself and the ones who await him at home, the embodiment of the character s inner conflict. This dissertation aims to discuss some image constructions related to both father and his prodigal son (au contraire), André, through the interaction between literature and psychoanalysis. To do so, some concepts referring to erotism, father s rule and myth will be approached, in order to perceive how the text apprehends the transgression in the narrative, emphasizing the heuristic potential of the piece for the understanding of both profane and sacred. It is tried to comprehend the way André s desire comes to be through his father s, insofar as this desire is one of the guiding elements of the work